Multiscale Dynamics of Blood Pressure Fluctuation Is Associated With White Matter Lesion Burden in Older Adults With and Without Hypertension: Observations From a Pilot Study - Jiang, Xin; Guo, Yi; Zhao, Yue; Gao, Xia; Peng, Dan; Zhang, Hui; Deng, Wuhong; Fu, Wen; Qin, Na; Chang, Ruizhen; Manor, Brad; Lipsitz, Lewis A.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: White matter lesions (WMLs) are highly prevalent in older adults, and hypertension is one of the main contributors to WMLs. The blood pressure (BP) is regulated by complex underlying mechanisms over multiple time scales, thus the continuous beat-to-beat BP fluctuation is complex. The association between WMLs and hypertension may be manifest as diminished complexity of BP fluctuations. The aim of this pilot study is to explore the relationships between hypertension, BP complexity, and WMLs in older adults. Method: Fifty-three older adults with clinically-diagnosed hypertension and 47 age-matched older adults without hypertension completed one MRI scan and one BP recording of 10 to 15 minutes when sitting quietly. Their cerebral WMLs were assessed by two neurologists using the Fazekas Scale based on brain structural MRI of each of their own. Greater score reflected higher WMLs grade. The complexity of continuous systolic (SBP) and diastolic (DBP) BP series was quantified using multiscale entropy (MSE). Lower MSE reflected lower complexity. Results: Compared to the non-hypertensive group, hypertensives had significantly greater Fazekas scores (F>5.3, p<0.02), and lower SBP and DBP complexity (F>8.6, p<0.004). Both within each group (β<-0.42, p<0.01) and across groups (β<-0.47, p<0.003), those with lower BP complexity had higher Fazekas score. Moreover, complexity of both SBP and DBP mediated the influence of hypertension on WMLs (indirect effects>0.25, 95% Confidence Intervals=0.06~0.50). Conclusion: These results suggest that diminished BP complexity is associated with WMLs and may mediate the influence of hypertension on WMLs. Future longitudinal studies are needed to examine the causal relationship between BP complexity and WMLs.